E-Government: Suatu Tinjauan Konsep dan Permasalahan - Cahyadi, Adi (Bina Nusantara University, 2003)
Like any other e-Business terms, e-Government is a term most likely to be over-exploited and this will tend to create a miss-perception in the way government and public views this emerging business concept. This relatively simple and short article tries to present in more detail to its readers the true concept of e-Government. Furthermore, this article will also explain the slow adoption rate of e-Government in a developing country such as Indonesia and offered a short term solution that is deemed appropriate